2021
DOI: 10.21037/atm-21-6081
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency inhibits microRNA-196b-5p which regulates ovarian granulosa cell hormone synthesis, proliferation, and apoptosis by targeting RDX and LRRC17

Abstract: Background: In polycystic ovary syndrome (PCOS), ovarian physiology is tightly linked to the metabolic disturbances observed in this disease. Vitamin D (VD) plays an important role in the regulation of ovulatory dysfunction and can influence genes involved in steroidogenesis in granulosa cells (GCs). However, its role in the proliferation and apoptosis of ovarian GCs is unclear. The present study aimed to investigate the role of in the hormone synthesis, proliferation, and apoptosis of ovarian GCs. Methods:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The red cluster was dominated by female, infertility, semen quality, PCOS, and VDR. Vitamin D could affect the synthesis of human hormones ( 32 ), the development of oocytes in women ( 13 ), the quality of sperm in men ( 33 ), and the implantation of the embryo ( 34 ). PCOS is one of the critical causes of infertility in childbearing women and its incidence was closely linked to vitamin D deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The red cluster was dominated by female, infertility, semen quality, PCOS, and VDR. Vitamin D could affect the synthesis of human hormones ( 32 ), the development of oocytes in women ( 13 ), the quality of sperm in men ( 33 ), and the implantation of the embryo ( 34 ). PCOS is one of the critical causes of infertility in childbearing women and its incidence was closely linked to vitamin D deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…miR-196a affects the proliferation, invasion, and apoptosis of tumor cells and is expected to become a new molecular marker or target for tumor diagnosis, treatment, and prognosis, indicating its potential in clinical applications [ 38 , 39 , 40 , 41 ]. Several studies have also reported that miR-196b is highly expressed in multiple malignant tumors and has the characteristics of an oncogene to promote tumorigenesis [ 42 , 43 , 44 ]. At present, the relevant studies mainly focus on cancer or tumors, and the roles of miR-196a-1 and miR-196b in bone and skeletal muscle and even in the motor system are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HS down-regulated miRNAs. It has been reported that miR-196b-5p can regulate the oxidative stress, apoptosis, and steroid production pathway of GCs, thus promoting follicular development and maturation ( 60 ). The miR-223-3p could regulate pyroptosis through NLRP3-Caspase 1-GSDMD signal axis ( 61 ).…”
Section: Discussionmentioning
confidence: 99%